2020
DOI: 10.3390/jfb11010014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Posterior Malleolus Fracture with the Finite Element Method

Abstract: The high demand for biodegradable implants in bone fracture fixations has dramatically increased the use of polymers for biomedical applications as well. However, the replacement of stainless steel and titanium screws by biodegradable materials represents one of the most critical aspects of biomechanics. In this study, the mechanical behavior of polycaprolactone (PCL) in tension and compression is examined. Driven by the advanced technology of computational mechanics, the fixation of the posterior malleolus fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There are many other possible applications, which could be applied for designing and testing of other implant models such as hip, knee, wrist, ankle, and spine. [18][19][20][21][22][23][24][25][26][27] A similar methodology to that explained in this paper could be utilized for teaching of FEM to BME students.…”
Section: Discussion Evaluation Of the Questionnairementioning
confidence: 99%
“…There are many other possible applications, which could be applied for designing and testing of other implant models such as hip, knee, wrist, ankle, and spine. [18][19][20][21][22][23][24][25][26][27] A similar methodology to that explained in this paper could be utilized for teaching of FEM to BME students.…”
Section: Discussion Evaluation Of the Questionnairementioning
confidence: 99%
“…After implantation, the ideal scaffold must elicit a negligible immune response, in order to avoid severe inflammatory responses that might reduce healing properties and/or cause material rejection [ 8 , 19 ]. Beyond their safety, scaffolds should provide appropriate structural support, and in certain cases, biomechanical cues, to promote the safe and effective reconstruction of a functional tissue in vivo [ 9 , 10 , 20 ]. A way to promote scaffold integration is to modify the chemical backbone of the biomaterial or the physicochemical properties of the surface to influence cell adhesion, migration, proliferation and differentiation in vivo [ 21 ].…”
Section: Requirements Of Scaffold For Tendon Repairmentioning
confidence: 99%
“…In this regard, tissue engineering strategies, including the concept of scaffold induced endogenous tissue repair, have gained popularity due to their assured biocompatibility and bioactivity [ 1 , 8 ]. Scaffolds can be used as a suitable platform, which permits cell-biomaterial interactions, cell adhesion, proliferation, and differentiation, while provoking a minimal degree of immune response [ 1 , 9 , 10 ]. Preliminary studies have shown that scaffolds may be used as an alternative augmentation, associated with significant therapeutic potential [ 9 ].…”
Section: Introductionmentioning
confidence: 99%